Menuju Komunitas Kolaboratif: Implikasi Teori Intersubjektivitas dalam Dilema Komunitas Religius Multikultur - Apriano, Alvian (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2024)
This article presents how philosophical thinking practically gives relational strength to multicultural religious communities. Maurice Merleau-Ponty talks about intersubjectivity, the benefits of which are so binding in inter-body relations. Steven McCormack talks about the importance of interpersonal communication as a strength of relationships within the community. David W. McMillan and David M. Chavis talk about the importance of "belonging" in the praxis of community. This article focuses on the question, "How can individuals in multicultural religious communities collaborate in the midst of dilemmas?" Indeed, the framework is built on Merleau-Ponty's theory of intersubjective philosophy. This will encourage collaboration in multicultural religious communities and leave behind primordial dilemmas that limit future community development steps. By analyzing the philosophy of intersubjectivity, we are offered the opportunity to transform past relationships and then make new meanings of them towards a collaborative community in the future.AbstrakArtikel ini menyajikan bagaimana pemikiran filsafat secara praktis memberi kekuatan terhadap relasi individu di dalam komunitas religius yang multikultur. Maurice Merleau-Ponty berbicara tentang intersubjektivitas yang manfaatnya begitu mengikat relasi antar-subjek. Steven McCormack berbicara tentang pentingnya komunikasi interpersonal sebagai penguat relasi individu dalam komunitas. David W. McMillan dan David M. Chavis berbicara tentang pentingnya “rasa memiliki” dari setiap individu di dalam praksis berkomunitas. Fokus artikel ini berangkat dari sebuah pertanyaan, “Bagaimana individu dalam komunitas religius yang multikultural dapat berkolaborasi di tengah dilema-dilema yang ada?” Tentunya, kerangka berpikirnya dibangun dari teori filsafat intersubjek Merleau-Ponty. Hal ini akan mendorong kolaborasi dalam komunitas religius yang multikultur dan meninggalkan dilema-dilema primordial yang membatasi gerak langkah pengembangan komunitas di masa depan. Dengan menganalisis filsafat intersubjektivitas, kita ditawari kesempatan untuk mengubah relasi di masa lalu dan kemudian memaknainya secara baru untuk menuju komunitas kolaboratif di masa depan.